2021
DOI: 10.3390/cancers13102382
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Applications to Improve the Treatment of Locally Advanced Non-Small Cell Lung Cancers

Abstract: Locally advanced non-small cell lung cancer patients represent around one third of newly diagnosed lung cancer patients. There remains a large unmet need to find treatment strategies that can improve the survival of these patients while minimizing therapeutical side effects. Increasing the availability of patients’ data (imaging, electronic health records, patients’ reported outcomes, and genomics) will enable the application of AI algorithms to improve therapy selections. In this review, we discuss how artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…As shown in Figure 7A, the keyword cluster view indicates that "cell lung cancer" #0 and "deep learning" #1 are the largest clusters, suggesting that the application of deep learning in non-small cell lung cancer may be a mature and significant topic in this research field. Currently, deep learning has been widely applied in the clinical diagnosis (16,37,38), treatment (35,39) and prognosis prediction (34,40) of lung cancer. Simultaneously, the Timeline View analysis (Figure 7B) reveals that AI in the field of lung cancer has consistently focused on clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 7A, the keyword cluster view indicates that "cell lung cancer" #0 and "deep learning" #1 are the largest clusters, suggesting that the application of deep learning in non-small cell lung cancer may be a mature and significant topic in this research field. Currently, deep learning has been widely applied in the clinical diagnosis (16,37,38), treatment (35,39) and prognosis prediction (34,40) of lung cancer. Simultaneously, the Timeline View analysis (Figure 7B) reveals that AI in the field of lung cancer has consistently focused on clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…AI can complement the TNM staging of lung cancer and provide prognostic prediction information. It has been reported that AI-assisted prognosis prediction is more accurate and e cient than traditional prognosis prediction based on clinical features(52). Kun-Hsing et al(53) obtained histopathological images from TCGA of 2,186 patients with lung adenocarcinoma and Lung squamous cell carcinoma and used a ML approach to analyze 9,879 quantitative image features and select the top features, and distinguish between shortterm survivors and long-term survivors with stage I adenocarcinoma or squamous cell carcinoma in the TCGA dataset.…”
mentioning
confidence: 99%